Квантовая когерентность и запутанные состояния в процессе внутрирезонаторной генерации третьей субгармоники - М. С. Геворгян (ՀՀ ԳԱԱ հրատ.)
Исследована динамика корреляции флуктуаций числа фотонов взаимодействующих мод для процесса внутрирезонаторной генерации третьей субгармоники. Показано, что в этой системе можно получить запутанные состояния поля по переменным числа фотонов. Исследованы также квантовая динамика числа фотонов, динамика квантовой энтропии и функции Вигнера стационарного состояния фундаментальной моды и моды третьей субгармоники. Հետազոտված է փոխազդող մոդերի ֆոտոնների թվերի ֆլուկտուացիաների կոռելացիայի դինամիկան երրորդ ենթահարմոնիկի երևույթի համար: Ցույց է տրված, որ այս համակարգում կարելի է ստանալ ֆոտոնների թվերի փոփոխականներով խճճված դաշտի վիճակներ: Հետազոտված է նաև ֆոտոնների թվերի և քվանտային էնտրոպիայի քվանտային դինամիկան, ինչպես նաև ֆունդամենտալ մոդի և երրորդ ենթահարմոնիկի մոդի ստացիոնար վիճակների Վիգների ֆունկցիաները: The dynamics of correlation of photon number fluctuations of interacting modes for the process of intracavity third subharmonic generation is studied. It is shown that the entangled field states by the variables of photon number can be obtained in this system. The quantum dynamics of the photons number, of the quantum entropy and of the Wigner function of the stationary states of the fundamental mode and of the third subharmonic mode are also studied. It is found that the dynamics of these values are highly dependent on the value of the coupling coefficient of the interacting modes. In the region of large interaction times, for large values of the coupling coefficient of the modes, it is shown that the third subharmonic mode localizes in the three-component state with the same probability of detection of the mode in each component of the state.
Keywords: Physics; Science; Optics; Light; Quantum Physics